2010
DOI: 10.1002/app.32193
|View full text |Cite
|
Sign up to set email alerts
|

Study on chain deformation of polyacrylamides in solutions and its flocculation performance during the flocculation process

Abstract: Effects of external conditions, solution concentration, solvent quality, added salt, and pH on the chain conformation dimension of two kinds of polyacrylamide (PAAm) flocculants, neutral-PAAm, and cationic-P(AAm-DMC) (DMC, 2-[(methacryloyloxy)ethyl] trimethylammonium chloride), in parent solutions and their flocculation performance for Kaolin suspensions have been investigated by Ubbelohde viscometer and spectrophotometer, respectively. It was found that a negative correlation existed between the flocculation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
4
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 27 publications
2
4
0
Order By: Relevance
“…Reduced internal repulsive forces allow the structure of HEM to be less rigid and have a more relaxed configuration which enhances bridging flocculation. The effect of NaCl observed in this study is similar to the effect of salt in other flocculation systems: It has been observed that the salts CaCl 2 , KCl and NaCl increase the flocculant effectiveness of cationic chitosan, cationic glucomannan, cationic starch, and cationic synthetic flocculant …”
Section: Resultssupporting
confidence: 83%
“…Reduced internal repulsive forces allow the structure of HEM to be less rigid and have a more relaxed configuration which enhances bridging flocculation. The effect of NaCl observed in this study is similar to the effect of salt in other flocculation systems: It has been observed that the salts CaCl 2 , KCl and NaCl increase the flocculant effectiveness of cationic chitosan, cationic glucomannan, cationic starch, and cationic synthetic flocculant …”
Section: Resultssupporting
confidence: 83%
“…11 In acidic or alkali solutions, large chain deformation occurs, which improves the interaction between the CPAM and the suspended particles. 32 This mechanism resulted in an increase in the flocculation efficiency in alkali conditions (Figure 3).…”
Section: Magnetic Separation Of Microalgaesupporting
confidence: 91%
“…It has been reported (in the flocculation of kaolin) that, at low concentrations, CPAM causes flocculation by bridging, while at high concentrations the main mechanism becomes charge neutralization . In acidic or alkali solutions, large chain deformation occurs, which improves the interaction between the CPAM and the suspended particles . This mechanism resulted in an increase in the flocculation efficiency in alkali conditions (Figure ).…”
Section: Resultsmentioning
confidence: 99%
“…As one of the most important types of water-soluble polymers, polyacrylamides (PAMs) have been widely and intensively utilized in the fields of wastewater treatment, papermaking, oil drilling, and textiles because of their good water solubility, high viscosity, and remarkable flocculation performance. Generally, PAMs can be tailormade by controlling the molar mass, chemical composition, as well as the type and ratio of the functional groups attached to the polymer backbone. , For example, high molar mass PAMs are one of the most commonly used organic flocculants, which play important and indispensable roles for the treatment and purification of wastewater with high efficiency and environmental friendliness . However, the inherent deficiencies originating from the linear molecular structure, such as low dissolution rate, and limited shear resistance are still unavoidable. …”
Section: Introductionmentioning
confidence: 99%